Temporal and Spatial Dynamics of Inflammasome Activation After Ischemic Stroke - Lu, Danli; Hu, Mengyan; Zhang, Bingjun; Lin, Yinyao; Zhu, Qiang; Men, Xuejiao; Lu, Zhengqi; Cai, Wei (Frontiers in Neurology, 2021)
Inflammasome represents a highly pro-inflammatory mechanism. It has been identified that inflammasome was activated after ischemic stroke. However, the impact of inflammasome on stroke outcomes remains contradictory. The participating molecules and the functioning arena of post-stroke inflammasome activation are still elusive. Blood samples from stroke patients were collected and analyzed with flow cytometry to evaluate the correlation of inflammasome activation and stroke outcomes. Stroke model was established on male C57/Bl6 mice with transient middle cerebral artery occlusion (tMCAO, 1h). Dynamics of inflammasome components, cell type and location of inflammasome activation, and the therapeutic effects of inhibiting post-stroke inflammasome executors were evaluated. We found that the level of inflammasome activation positively correlated with stroke outcomes. Post-stroke inflammasome activation peaked at 3-5 day with participation of multiple components. Macrophage that infiltrated into the ischemic lesion was the main arena for post-stroke inflammasome activation. Caspase-1 and -11 served as main executing enzymes and inhibiting Caspase-1/-11 signaling efficiently suppressed DAMPs induced macrophage inflammasome and displayed neuroprotection to stroke models. Inflammasome activation plays a detrimental role in stroke pathology. Targeting post-stroke inflammasome executing enzymes fitting in the dynamics of macrophage may obtain potential and efficient therapeutic effects.